Aetiological Factors of Infertility: A Study done in Bangabandhu Shekh Mujib Medical University (BSMMU) Hospital - A Tertiary Level Hospital in Bangladesh - Anwar, Begum Rokeya; Fatima, Parveen; Afza, Nasim; Begum, Naznen; Kulsum, Syeda Umme; Parveen, Shaila (Journal of Dhaka Medical College, 2013)
J Dhaka Medical College, Vol. 21, No. 2, October, 2012, Page 152-155 DOI: http://dx.doi.org/10.3329/jdmc.v21i2.15337